Smart Industry Requires Fast Response from Research to Innovation - Gregor, Milan; Medvecky, Stefan; Grznar, Patrik; Gregor, Tomas (Communications - Scientific letters of the University of Zilina, 2017)
Factories of the Future (FoF) gradually advance towards reality. The theoretical concepts leave research laboratories and quickly find their field in industry. This paper introduces Smart Factory issues. The authors in its first part summarized information from research and main trends in the area of advanced manufacturing systems. Second part of the paper shows the results from authors own research conducted in co-operation of Mechanical Engineering Faculty of the University of Zilina and its Spin Off, The Central European Institute of Technology - CEIT, a.s. The paper shows chosen results from implementation of research results in innovation of internal logistics in VW Group.